2019
DOI: 10.26905/abdimas.v4i1.3231
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Mesin Sangrai Kopi Pada Ukm Kopi Bubuk “Bias Kahyangan” Di Desa Arjowinangun – Kota Malang

Abstract: AbstrakBudaya minum kopi atau ngopi sudah lama dipercaya masyarakat dan terbukti bermanfaat meningkatkan kesehatan dan kesegaran bagi tubuh. Oleh karena itu kebutuhan konsumen pada kopi bubuk di kota Malang cukup besar sehingga banyak sekali produsen kopi bubuk bermunculan mulai dari perusahaan besar sampai home industri. UKM Kopi bubuk merek "Bias Kahyangan" adalah usaha dagang kopi bubuk murni yang berlokasi di desa Arjowinangun Kota Malang. Dalam kegiatan produksinya, proses sangrai kopi masih dilakukan ole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…Quality roasting results can be achieved through an even roasting process that is carried out at the right time and at the right heating temperature (± 80⁰C). Therefore, to control the quality of roasted coffee, it is necessary to roast using a roasting machine that has a rotating tube so that the temperature in the tube is even and equipped with temperature control [12]. [13] reported that in 114 minutes at a temperature of 205 0 C, the process of roasting arabica and robusta coffee beans was carried out using a rotating cylindrical coffee roaster with electricity as the heat source.…”
Section: Roasting Temperature Processmentioning
confidence: 99%
“…Quality roasting results can be achieved through an even roasting process that is carried out at the right time and at the right heating temperature (± 80⁰C). Therefore, to control the quality of roasted coffee, it is necessary to roast using a roasting machine that has a rotating tube so that the temperature in the tube is even and equipped with temperature control [12]. [13] reported that in 114 minutes at a temperature of 205 0 C, the process of roasting arabica and robusta coffee beans was carried out using a rotating cylindrical coffee roaster with electricity as the heat source.…”
Section: Roasting Temperature Processmentioning
confidence: 99%
“…Wafiroh et al (2023) stated that business capital is very important, but production costs have a very influential role in MSME income. Hariyanto et al (2019) in his research in the form of designing coffee roasting machines, succeeded in increasing UKM income from Rp. 65,000, -per day to Rp.…”
Section: Figure 2 Cassava Cutter and Its Operationmentioning
confidence: 99%
“…Pelatihan manajemen keuangan UMKM Kopi juga menjadi salah satu kegiatan yang cukup penting, untuk memastikan UMKM dapat mengelola keuangan secara baik (Sa'diyah et al 2020). Pendampingan berupa intervensi inovasi teknologi dalam mendukung petani misalkan dikenalkan mesin sangrai atau roasting (Hariyanto et al 2019). Pendampingan yang dilakukan dalam pengabdian ini sebagai upaya mendorong adanya inovasi produk olahan kopi oleh petani, untuk meningkatkan variasi produk pertanian.…”
Section: Pendahuluanunclassified